Literature Study: The Influence of Use Animated Video Learning Media on Improving Student Learning Outcomes - Athiyyah Fadhilah, Nur; Atmasani, Dian; Makmur, Elfira; Nurfauziah, Nurfauziah (Jurnal Pendidikan dan Profesi Keguruan, 2025)
This study aims to review literature on the influence of utilizing animated video learning media in improving student learning outcomes and to identify the inhibiting factors in its implementation in the learning process. The research method used is a qualitative literature review with a qualitative approach. The data used were 13 articles selected based on relevance, limited to publications from the last five years (2021–2025), discussing the impact of animated video learning media on student learning outcomes. Based on the literature review results, it can be concluded that the use of animated video learning media has positive effect on students’ learning outcomes. This can be seen from the results of students’ post-test after learning using animated videos. However, there are several inhibiting factors in the implementation of animated video learning media, including limited facilities and infrastructure, teacher competence, and varying levels of student comprehension.